2012
DOI: 10.3389/fcimb.2012.00133
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics and stx Phage Characterization of LEE-Negative Shiga Toxin-Producing Escherichia coli

Abstract: Infection by Escherichia coli and Shigella species are among the leading causes of death due to diarrheal disease in the world. Shiga toxin-producing E. coli (STEC) that do not encode the locus of enterocyte effacement (LEE-negative STEC) often possess Shiga toxin gene variants and have been isolated from humans and a variety of animal sources. In this study, we compare the genomes of nine LEE-negative STEC harboring various stx alleles with four complete reference LEE-positive STEC isolates. Compared to a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
108
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(134 citation statements)
references
References 92 publications
14
108
2
1
Order By: Relevance
“…Table 1 lists stx phages whose complete sequences are available in GenBank. Recent comparisons of whole genomes have confirmed that stx phages share a general genomic organization, but with a significant degree of sequence diversity, reinforcing the concept of their mosaic nature (Ahmed et al, 2012;Smith et al 2012;Steyert et al, 2012;Cooper et al, 2014;Tozzoli et al, 2014a). Furthermore, some studies identified different types of stx phages harbouring even the same stx 2 subtype (Ahmed et al, 2012;Tozzoli et al, 2014b).…”
Section: Diversity Of Stx Phagesmentioning
confidence: 92%
See 3 more Smart Citations
“…Table 1 lists stx phages whose complete sequences are available in GenBank. Recent comparisons of whole genomes have confirmed that stx phages share a general genomic organization, but with a significant degree of sequence diversity, reinforcing the concept of their mosaic nature (Ahmed et al, 2012;Smith et al 2012;Steyert et al, 2012;Cooper et al, 2014;Tozzoli et al, 2014a). Furthermore, some studies identified different types of stx phages harbouring even the same stx 2 subtype (Ahmed et al, 2012;Tozzoli et al, 2014b).…”
Section: Diversity Of Stx Phagesmentioning
confidence: 92%
“…argW, potC, prfC, serU, ssrA, wrbA, yciD, yecD, yecE, yjbM, ynfH and Z2577 (Recktenwald & Schmidt, 2002;Koch et al, 2003;Ahmed et al, 2012;Steyert et al, 2012;Cooper et al, 2014).…”
Section: Insertion Site Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Strains laking eae are named as LEE-negative STEC. Steyert et al (2012) demonstrate that the overall genome content, phage location, and combination of potential virulence factors are variable in this strains group.…”
mentioning
confidence: 99%